Positive Identification of UV-Generated, Non-Hydrogen-Bonded Isomers of o-Hydroxybenzaldehyde and o-Hydroxyacetophenone - Lapinski, Leszek (2010)
Non-hydrogen-bonded isomers were photogenerated by UV (λ > 335 nm) irradiation of o-hydroxybenzaldehyde (salicylaldehyde) and o-hydroxyacetophenone monomers isolated in low-temperature Ar matrixes. These photoisomerizations were found to be photoreversible. Upon shorter wavelength (λ > 235 nm or λ > 270 nm) UV irradiation, the initial forms of the compounds (with intramolecular hydrogen bonds) were partially repopulated. The structures of the photogenerated non-hydrogen-bonded isomers of both compounds were positively identified by comparison of their IR spectra with the spectra theoretically calculated [at the DFT(B3LYP)/6-311++G(2d,p) level] for all possible non-hydrogen-bonded isomers of the studied compounds. The experimental IR spectra of the photoproducts generated from o-hydroxybenzaldehyde and o-hydroxyacetophenone are very well reproduced only by the theoretical spectra predicted for the isomers with both OH and formyl (or acetyl) groups rotated by 180°, with respect to the initial, most stable hydrogen-bonded conformer. Excellent agreement between experiment and theoretical prediction provides a basis for a very reliable identification of the photoproduced isomers of o-hydroxybenzaldehyde and o-hydroxyacetophenone.